Pre-Questioning Strategy On Reading Comprehension Achievement At The Fourth Semester Of English Program Study STKIP Taman Siswa Bima - Waliyudin; annisah (JURNAL PENDIDIKAN BAHASA, 2018)
This study was conducted to investigate the effect of Pre-questioning on Reading Comprehension Achievement of the Fourth Semester Students at English Program Study STKIP Taman Siswa Bima. The aimed of this study were to investigate the effects of pre-questioning students’ on the reading comprehension achievement of the Fourth Semester Students at English Program Study STKIP Taman Siswa Bima 2017/2018. The forms of questions were in multiple choice and essay, multiple choice used for reading comprehension tests and essay used for Pre-questioning tests. The method used in this study was experimental design. The data were processed and analyzed according to these steps: taking the data, checking, scoring, tabulating using SPSS program and taking the conclusion based on the statistic result. The result of this study shows that “the Pre-questioning has a significant effect on the students’ reading comprehension achievement.